SENSITIVE TO FREEZING6 Integrates Cellular and Environmental Inputs to the Plant Circadian Clock - Knight, H.; Thomson, A.J.; McWatters, H.G. (Plant Physiology, 2008)
The sensitive to freezing6 (sfr6) mutant of Arabidopsis (Arabidopsis thaliana) is late flowering in long days due to reduced expression of components in the photoperiodic flowering pathway in long-day photoperiods. Microarray analysis of gene expression showed that a circadian clock-associated motif, the evening element, was overrepresented in promoters of genes down-regulated in sfr6 plants. Analysis of leaf movement rhythms found sfr6 plants showed a sucrose (Suc)-dependent long period phenotype; unlike wild-type Arabidopsis, the clock in sfr6 plants did not have a shorter rhythm in the presence of Suc. Other developmental responses to Suc were unaltered in sfr6 plants, suggesting insensitivity to Suc is restricted to the clock. We investigated the effect of sfr6 and Suc upon clock gene expression over 24 h. The sfr6 mutation resulted in reduced expression of the clock components CIRCADIAN CLOCK ASSOCIATED1, GIGANTEA, and TIMING OF CAB1. These changes occurred independently of Suc supplementation. Wild-type plants showed small increases in clock gene expression in the presence of Suc; this response to Suc was reduced in sfr6 plants. This study shows that large changes in level and timing of clock gene expression may have little effect upon clock outputs. Moreover, although Suc influences the period and accuracy of the Arabidopsis clock, it results in relatively minor changes in clock gene expression.
EPrint Processing Status: Author unable to supply full text